Common Property: English as a Lingua Franca in Ghana, The Perspective of the College of Education Tutor - G, Donkor; C.F, Lomotey (European Scientific Journal, ESJ, 2021)
The study sought to investigate English as a Lingua Franca (ELF) in the classroom of the College of Education tutor in Ghana using the Ashanti Region as a case. A total of 48 participants were selected from 9 Colleges of Education for the study using purposive sampling. Data were collected using a six-point Likert-type scale questionnaire and a semi-structured interview guide. Data analysis and presentation of results were done using mean and standard deviations. The study revealed that intercultural awareness was important for language users. These findings could be interpreted as the changing conceptualizations of English language and pedagogy among language tutors in various contexts. Tutors’ awareness of the need to communicate in English was not restricted to native speaker communities. It was recommended that tutors should seek ways of acquiring attitudes that can help them create a congenial atmosphere for teaching and learning as/ this is needed by students to understand what their tutors teach them.